Multi Center Computer Guided Analysis of Site Distribution in Isolated Mandibular Fracture (Medical Forum Monthly, 2022)
Objective: To determine the site distribution in isolated mandible fracture using multi center computer guided analysis among patients presenting at tertiary care hospital of Karachi, Pakistan.Study Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at multicenter Tertiary Care Hospitals in Karachi from 1-1-2021 to 1-7-2021.Materials and Methods: Data was collected after obtaining ethical approval from institutional ethical review committee. Verbal informed consent was obtained. Total of 500 OPGs (Orthopantomagram) from various tertiary care hospitals in Karachi were collected. Data was collected in the form of radiographs or soft copies in a removable storage device. Computer based analysis of OPGs were done. The collected OPGs were assessed for lines of propagation of fracture and pattern of mandibles fractures. All data were collected and noted on a pre-designed profarma by researcher.Results: Average age of patients was 30.37±12.37 years. Out of 500 patients 344(69%) were male and 156(31%) were female patients. Most common sites of mandibular fracture were parasymphysis 118(23.6%), body 79(15.8%), sub-condyle 70(14%), angle 48(9.6%) while in multiple site fractures symphysis/parasymphysis was the frequent combination 37(7.4%).Conclusion: Majority of young male patients suffered from mandibular fractures. RTA (road traffic accident) was the most prevalent cause of mandibular fracture, followed by falls. Parasymphysis, body and sub-condyle were the most frequently fractured sites.